Thermal sintering of printable copper for enhanced conductivity of FTO coated glass substrates - Bahaa Abbas (Journal of Materials Science: Materials in Electronics, 2019)
Copper inks potentially provide a cost effective replacement to silver for printed electronic circuits. In glass based applications such as PV or smart glass, it can provide a means of conductivity enhancement or additional functionality. Three inks consisting of a mixture of nano and micro copper particles were systematically studied to examine the relationship between sintering temperature, sintering time and gaseous environment on the electrical qualities of the sintered printed films deposited on FTO coated glass. There is a definite interaction between the particulate nature of the ink, the sintering conditions and the conductive properties of the film. Films containing only nano-particles provide the most conductive films with optimum sintering conditions of temperatures of 225 °C for 60 min. The inclusion of micro particles increased the ideal sintering temperature but lowered the sintering time. An ink containing an equal mixture of nano and micro particles exhibited the lowest performance and this could be attributed to partial oxidation of the nano-particles along the conductive path, which occurs as a result of the presence of the micro particles.